Disentangling Parsing and Grammar in Subject Pronouns Interpretation in Italian - Elisa Di Domenico; Carla Contemori Contemori (Quaderni di Linguistica e Studi Orientali, 2023)
In the present study, we investigate if and how null and overt subject pronouns interpretation preferences in Italian can be influenced by two factors: (i) the presence of c-commanding antecedents (Rizzi 2018) and (ii) the ‘impatient parser’ (Sorace and Filiaci 2006; Fedele and Kaiser 2014). To disentangle the effects of c-commanding antecedents and of the ‘impatient parser’, we compare experimental conditions differing for only one of the two factors. The comparison demonstrates that c-commanding antecedents influence the interpretation of null pronouns but not the interpretation of overt pronouns, while no effect of the impatient parser is found for either null or overt pronouns. In addition, we found that external referent interpretation preferences are modulated by Principle C effects for null and overt pronouns, albeit to different degrees. External referent choices also increase when an